2006
DOI: 10.4102/ojvr.v73i2.161
|View full text |Cite
|
Sign up to set email alerts
|

The fluorescent detection of <i>Paradiplozoon</i> sp. (Monogenea: Diplozoidae) attachment clamps' sclerites and integumental proteins : research communication

Abstract: In the genus Paradiplozoon, few hard structures are present therefore most of the taxonomic studies have focused on the unique ultrastructure of the sclerites. Alcohol-fixed specimens were transferred to BSA-saline for 5 min. before staining indefinitely with 5 µl WGA-TRX, 5 µl SYTO 9 and 5 µl of Cal co fluor White M2R. Rhodamine, Fluorescein and DAPI bandpass filters on the microscope enabled selective light wavelength illumination of the three flourochromes by a mercury light source. This method provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…sclerites were composed of chitin [55]; however, later work showed that the sclerites of D. paradoxum from the same family consisted of a resilin-like protein [32]. More recently, studies on the chemical composition of monogenean clamps have shown that they are formed of scleroproteins, probably stabilized by tyrosyl residues in dityrosine [29, 56].…”
Section: Discussionmentioning
confidence: 99%
“…sclerites were composed of chitin [55]; however, later work showed that the sclerites of D. paradoxum from the same family consisted of a resilin-like protein [32]. More recently, studies on the chemical composition of monogenean clamps have shown that they are formed of scleroproteins, probably stabilized by tyrosyl residues in dityrosine [29, 56].…”
Section: Discussionmentioning
confidence: 99%
“…Lyons [59] and Shinn et al [60] suggested that the sclerotized haptoral elements of gyrodactylids are composed of keratin–like proteins. Regarding the protein composition of the sclerites of diplozoids, two studies have suggested that these structures are composed of either chitin [61] or resilin–like proteins [62], which is similar to the composition of arthropod exoskeletons. Terrestrial and marine marcoinvertebrates have been shown to incorporate elements into their exoskeletons as a means of detoxification [6365] and structural support [5356].…”
Section: Discussionmentioning
confidence: 99%
“…Various papers have addressed the influence of methods on the measurements of specimens (Bakke 1988;Criscione and Font 2001;Fagerholm 1979;Fagerholm and Lövdahl 1984;Justine 2005Justine , 2007 or the processing of monogenean sclerites (García-Vásquez et al 2011;Kritsky et al 1978;Maillard et al 1982;Malmberg 1957;McDougal and Mizelle 1969;Milne and Avenant-Oldewage 2006;Mo and Appleby 1990;Shinn et al 1993;Richards and Chubb 1995;Rohde 1987). The interest in describing new methods is still alive and many recently published works address specific parasites or methods (Albuquerque et al 2009;Bruno et al 2006;Cribb et al 2004;Deveney and Whittington 2001;Galli et al 2006;Galli et al 2007;Parker et al 2010;Snyder and Clopton 2005;Wong et al 2006).…”
Section: Introductionmentioning
confidence: 97%